The Qur’an: An Oral Transmitted Tradition Forming Muslims Habitus - Dweirj, Lina (Religions, 2023)
This paper examines the relation between religious practices and the forming of moral dispositions in light of the Qur’an. Using Bourdieu’s concept of habitus, this paper explains the way religious practices mentioned in the Qur’an could form moral dispositions for Muslims. The question that this research aims to answer is whether being a Muslim has anything to do with how he is expected to behave in society. It also investigates how central the Qur’an is in Muslims’ lives. Moreover, it discusses how and why Muslims act and what guides their practices and actions. This paper aims to clarify the ethical, moral and spiritual consequences of embodying religious practices. For example, practices like prayer and charity may give Muslims moral direction and help them be good citizens.